Amphibians as a model to study the role of immune cell heterogeneity in host and mycobacterial interactions. (February 2023) - Paiola, Matthieu; Dimitrakopoulou, Dionysia; Pavelka, Martin S.; Robert, Jacques
Abstract: Mycobacterial infections represent major concerns for aquatic and terrestrial vertebrates including humans. Although our current knowledge is mostly restricted to Mycobacterium tuberculosis and mammalian host interactions, increasing evidence suggests common features in endo- and ectothermic animals infected with non-tuberculous mycobacteria (NTMs) like those described for M. tuberculosis . Importantly, most of the pathogenic and non-pathogenic NTMs detected in amphibians from wild, farmed, and research facilities represent, in addition to the potential economic loss, a rising concern for human health. Upon mycobacterial infection in mammals, the protective immune responses involving the innate and adaptive immune systems are highly complex and therefore not fully understood. This complexity results from the versatility and resilience of mycobacteria to hostile conditions as well as from the immune cell heterogeneity arising from the distinct developmental origins according with the concept of layered immunity. Similar to the differing responses of neonates versus adults during tuberculosis development, the pathogenesis and inflammatory responses are stage-specific in Xenopus laevis during infection by the NTM M. marinum . That is, both in human fetal and neonatal development and in tadpole development, responses are characterized by hypo-responsiveness and a lower capacity to contain mycobacterial infections. Similar to a mammalian fetus and neonates, T cells and myeloid cells in Xenopus tadpoles and axolotls are different from the adult immune cells. Fetal and amphibian larval T cells, which are characterized by a lower T cell receptor (TCR) repertoire diversity, are biased toward regulatory function, and they have distinct progenitor origins from those of the adult immune cells. Some early developing T cells and likely macrophage subpopulations are conserved in adult anurans and mammals, and therefore, they likely play an important role in the host-pathogen interactions from early stages of development to adulthood. Thus, we propose the use of developing amphibians, which have the advantage of being free-living early in their development, as an alternative and complementary model to study the role of immune cell heterogeneity in host-mycobacteria interactions. Highlights: An update on the mycobacteria diversity and biology, emphasizing non-tuberculous mycobacteria (NTMs). Impact of mycobacteriosis on amphibians in the wild and in research facilities. Overview of interactions between NTMs and amphibian hosts. Amphibians as models to investigate mycobacteria-host interactions.